'Anything Westminster can do we can do better': the Scottish climate change act and placing a sub-state nation on the international stage. Issue 6 (19th September 2021) - Nash, Sarah Louise
ABSTRACT: In 2009, Scotland passed, at the time, the world's most ambitious climate change legislation, gaining significance due to its high-reaching targets to reduce greenhouse gas emissions and a complex bureaucratic set-up. It was the most complex legislation to pass through the Scottish Parliament since its inception, and a landmark bill of the Scottish National Party's first term in government. Based on documentary research and interviews with policymakers and stakeholders, I use the Multiple Streams Model against the context of multi-level governance to analyse the emergence of the Climate Change Act in Scotland and what factors influenced its form, analysing problem, policy, and politics streams as well as structural and cultural-institutional entrepreneurship. The Act's creation was tied up in attempts to position Scotland, a sub-state nation, on the international stage, with the legislation framed not only as necessary in the face of climate change, but an opportunity for Scotland.